Criação de mercado de créditos de biocombustível avançado para geração de economia financeira e ambiental no comércio de etanol entre Brasil e Estados Unidos - Haddad, João Paulo Rocha (2015)
Ethanol trading between Brazil and United States is strongly guided by a reg-ulatory asymmetry, which valorizes the Brazilian product through the creation of an American demand for it. This demand is originated from the Renewable Fuel Stand-ard (RFS) program’s mandates for biofuels consumption. RFS classifies the Brazili-an ethanol as an Advanced Biofuel, turning this product more valuable in the Unit-ed States than the one produced locally from the corn starch. What differentiates one product from the other is the producing process, which gives to the sugar cane ethanol the status of a less CO2 emitting life cycle biofuel when compared do the ethanol made from corn. Although there is a difference between both production systems, the final product is the same: Anhydrous Fuel Ethanol. Therefore, when the American demand for the sugar cane product causes a deficit in the Brazilian balance of supply and demand, it makes necessary an importation of ethanol from the US. This ethanol’s round trip occurs simultaneously, which allows to consider that there is a redundant flow of product between both countries, with financial and environmental expenses that could be avoided. Given that the American interest for the Brazilian product lies on the lower emission life cycle of the sugar cane ethanol, the redundant flow mentioned before could be swapped for transactions of Ad-vanced Biofuel Credits, a new idea which is designed throughout this work. For the Credits traded from Brazil to the United States, the latter will account on it’s balance the emissions of CO2 related to an equivalent volume of ethanol from sugar cane, while Brazil assumes the emissions for the same volume of ethanol from corn starch. The substitution of physical product trading for paper trading is the source for the savings proposed by the title of this work.